ORANG DENGAN GANGGUAN JIWA: KONSTRUKSI PERTANGGUNGJAWABAN PIDANA DALAM KONSTELASI HUKUM PIDANA NASIONAL - Yenny Fitri Z (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: Criminal cases involving perpetrators with mental disorders (OD-GJ) are increasing in number and variety in Indonesia. The perpetrators not only damaged other people's property, but also abused them and killed them. The regulation of national criminal law (Indonesia) still leaves many problems. If an OD-GJ person commits a crime, then the norm of abolishing a crime (Article 44 of the Criminal Code) applies. If this accountability is erased, then the reason for forgiving the offender will apply. That is, the offender has reasons to erase his guilt so that he cannot be punished. This research wants to see how the dimensions of contemporary national criminal law actually view OD-GJ when committing a criminal act. Can accountability be pinned on him. So, what are the prospects for regulation if the crime is committed by OD-GJ. This research is based on normative methods using secondary data and collected through literature study. This research found that criminal liability for people with mental disorders cannot be treated equally, but rather is adjusted to the qualifications of the mental disorder and the form of the crime he committed. If at present, criminal acts committed by someone who is in an OD-GJ condition can eliminate his criminal responsibility, then in accordance with developments there should have been various reforms made regarding legal arrangements for perpetrators of crimes with this mental disorder.